Changes of the immunological barrier of intestinal mucosa in rats with sepsis - Jiang, Long-yuan (Second Affiliated Hospital of Zhejiang University School of Medicine, 2010)
BACKGROUND: Sepsis has become the greatest threat to in-patients, with a mortality of over 25%. The dysfunction of gut barrier, especially the immunological barrier, plays an important role in the development of sepsis. This dysfunction occurs after surgery, but the magnitude of change does not differentiate patients with sepsis from those without sepsis. Increased intestinal permeability before surgery is of no value in predicating sepsis. The present study aimed to observe the changes of intestinal mucosal immunologic barrier in rat models of sepsis induced by cecal ligation and puncture. METHODS: Sixty Sprague-Dawley rats were randomly divided into a sepsis group (n=45) and a control group (n=15). The rats in the sepsis group were subjected to cecal ligation and puncture (CLP), whereas the rats in the control group underwent a sham operation. The ileac mucosa and segments were harvested 3, 6 and 12 hours after CLP, and blood samples were collected. Pathological changes, protein levels of defensin-5 (RD-5) and trefoil factor-3 (TFF(3)) mRNA, and lymphocytes apoptosis in the intestinal mucosa were determined. In an additional experiment, the gut-origin bacterial DNA in blood was detected. RESULTS: The intestinal mucosa showed marked injury with loss of ileal villi, desquamation of epithelium, detachment of lamina propria, hemorrhage and ulceration in the sepsis group. The expression of TFF(3) mRNA and level of RD-5 protein were decreased and the apoptosis of mucosal lymphocyte increased (P<0.05) in the sepsis group compared with the control group. Significant differences were observed in RD-5 and TFF(3) mRNA 3 hours after CLP and they were progressively increased 6 and 12 hours after CLP in the sepsis group compared with the control group (P<0.05, RD-5 F=11.76, TFF(3) F=16.86 and apoptosis F=122.52). In addition, the gut-origin bacterial DNA detected in plasma was positive in the sepsis group. CONCLUSION: The immunological function of the intestinal mucosa was impaired in septic rats and further deteriorated in the course of sepsis.